Optimalisasi Kinerja Karyawan Melalui Kepemimpinan Islami dan Pelatihan: Peran Penting Kepuasan Kerja di KSU Ja'far Medika Syariah Karanganyar - Sujarwanto, Sujarwanto; Sutianingsih, Sutianingsih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The purpose of this study is to evaluate the influence of employee training and Islamic leadership on employee performance, by utilizing the intervening variable of employee job satisfaction. This study uses a quantitative methodology and is causal associative. It is known that this study involved 84 employees as a sample. Proper and trustworthy questionnaires are used to collect data. Multiple linear regression analysis techniques were used to analyze the data. The results of the study show that: Employee performance increases significantly due to the positive and significant influence caused by employee training, Islamic leadership and job satisfaction. Job satisfaction mediates a statistically significant relationship between training, Islamic leadership and performance. Keywords: Employee training, Islamic leadership, job satisfaction, employee performance